Tinea incognita with secondary bacterial infection - Daniel A Nadelman (Wolters Kluwer Medknow Publications, 2022)
Tinea incognita is a phenomenon occurring when a fungal infection is erroneously treated with topical corticosteroids. This worsens the underlying infection without becoming clinically apparent until treatment is withdrawn, in which case the tinea infection becomes acutely symptomatic. We herein report a case of tinea incognita in a young woman treated with high-potency topical corticosteroids, leading to worsening dermatophyte infection and coinfection with Klebsiella oxytoca. The resulting infection required aggressive oral and topical antimicrobial treatment before resolving. This case illustrates the potentially harmful sequelae of using high-potency topical corticosteroids without first ruling out tinea infection.